Efficacy and safety of high-dose ilaprazole-amoxicillin dual therapy for Helicobacter pylori eradication: a prospective, single-center, randomized trial - Cheng, Jianping; Fan, Chanjuan; Huang, Kun; Zhai, Lili; Wang, Hui; Xie, Dongling; Cai, Yong; Li, Zhen; Bai, Qixuan; Wang, Pan; Ding, Haiou (Frontiers in Pharmacology, 2023)
Background: Until now, there have been no randomized controlled trials directly evaluating the efficacy of high-dose ilaprazole-amoxicillin dual therapy (HT) in comparison to other standard treatments for Helicobacter pylori (H. pylori) infection.This study aimed to compare the effectiveness and safety of HT with bismuth quadruple therapy (BQT) as an initial treatment for H. pylori.Methods: This single-center, prospective, randomized clinical controlled trial recruited 225 consecutive patients. They were assigned to either HT group (ilaprazole, 10 mg, twice daily; amoxicillin 1,000 mg, three times daily) or BQT group (compound bismuth aluminate granules, 2.6 g, three times daily; ilaprazole, 5 mg, twice daily; amoxicillin, 1,000 mg, twice daily; clarithromycin, 500 mg, twice daily) for 14 days. The 13 C-urea breath test assessed eradication success four weeks after treatment. The primary outcome focused on the eradication rate, with secondary outcomes including safety and compliance.Results: From FebruaryDecember 20232 to MarchDecember 2023, 228 subjects were screened, and 225 were randomized. The HT and BQT groups showed eradication rates of 76.3% and 61.3% (p = 0.015) both by intention-to-treat (ITT) analysis and perprotocol (PP) analysis. HT was non-inferior to BQT in both ITT and PP analyses. HT was associated with fewer adverse events than BQT (27.2% vs. 81.8%, p = 0.002). The most commonly reported adverse events (incidence ≥2%) wasere black stool (1.8% with HT vs. 57.7% with BQT, p < 0.001) and bitter taste of mouth (3.5% vs. 60.4%, p < 0.001). There was no significant difference in compliance between the two groups 3 (89.5% vs. 92.8%, pP = 0.264).The 14-day HT treatment demonstrates better efficacy in H. pylori eradication treatment and improved safety and compliance compared to BQT. The results provide supporting evidence for 14-day HT can be potentially considered as a first-line regimen for empirical treatment.The study was registered in the Chinese Clinical Trial Registry (trial registration number: ChiCTR2200066284).